A Kurdish Sufi Master and His Christian Neighbors. (1st June 2018) - Soleimani, Kamal
Abstract : This paper examines the religiopolitical views of sheikh Ubeydullah of Nehri, the leader of the 1880 Kurdish uprising. The paper uses new primary sources, which allow for a more coherent picture of the scopes and limits of sheikh Ubeydullah's views on a number of key issues, especially on topics of religious universalism and tolerance, Kurdish education, and Kurdish nationalism. The paper uses archival research and primary sources to challenge an existing scholarly view that the Sheik uprising was driven by his alleged anti-Christian views similar to those found among Turks. Instead, the paper argues that his views contrasted sharply with these and were, instead, rooted more in a Rum-type religious universalism that was actually more hospitable to Christians. This paper particularly focuses on the sheikh's relation with non-Muslims throughout and makes extensive use of the transcriptions of a three-hour conversation between the sheikh andan American missionary figure. This long conversation unveils much about the motivations behind the 1880 Kurdish uprising and touches upon Ubeydullah's previously unknown and, interestingly, unorthodox thoughts about religious universalism and religious tolerance.